Kajian Potensi dan Tantangan Pariwisata di Kota Singkawang - Yosafat Fantony; Lucky Nugroho; Zulfahmi Zulfahmi (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine the challenges and opportunities of tourism in Singakawang, West Kalimantan. The method used in this research is using descriptive qualitative. Furthermore, the problem formulations used in this study include (i) How is the tourism sector in Singkawang; (ii) What are the advantages of the tourism sector in Singkawang; (iii) How to improve the tourism sector in Singkawang? Furthermore, the results of this study found that Singkawang has excellent tourism potential both from the aspect of tourist attractions, nature tourism, culinary tourism and besides that tourism in Singkawang must also be supported by various elements which include (i) Accommodation, (ii) Transportation, (iii) Transportation, (iv) Attractions and landmarks, (v) Tourist Information Centers, (vi) Restaurants and Eateries, (vii) Shopping Facilities, (viii) Recreation and Entertainment, (ix) Infrastructure for Safety and Security, (x) Universal Accessibility. Therefore, the implication of this research is to know the condition of tourism in Singkawang and the advantages of its tourism sector, as well as to know the supporting factors that can improve the tourism sector in Singkawang. In addition, the novelty of this research is related to the tourism sector in Singkawang whose information is still limited.